Culture and local development - Greffe, Xavier; Pflieger, Sylvie; Noya, Antonella (Local economic and employment development., 2005)
This publication highlights the impact of culture on local economies and the methodological issues related to its identification. In particular, the book demonstrates that the contemporary contribution of culture to economic development is not limited to attracting tourists, but that it increasingly acts as a catalyst for other activities to further develop through territorial clusters. It also demonstrates the power of culture as a tool for the social integration of distressed people and communities, thus contributing to sustainable development. Building on recent international case studies, this publication shows how public policies can foster culture as a lever for local economic development in terms of partnerships, tax relief, and other innovative instruments. The book also sets out the implications for national governments in the fields of education and intellectual property rights.--Publisher's description.